Part 2: The development of an active pedagogy. Issue 3 (1st December 2019) - Infante Mora, Eva; Muñoz Andrade, Juan; Greenwood, Davydd; Feldman, Richard; Ivanchikova, Melina; Cívico Gallardo, Jorge; García Saez, Purificación
Abstract : This section discusses how the changing students' experiences necessitated a rethinking of the educational programme and the development of an active pedagogy. The reform used two powerful instruments: an adaptation of the Common European Framework of Reference for Languages, which allows the language coordinator to evaluate the linguistic needs of students upon arrival (and the students to recognise their own strengths and weaknesses) and to design strategies that help them improve during the semester; and the new Common Framework for Intercultural Learning, inspired by the former, which allows students to acquire and improve behavioural intercultural skills through self-managed research practices. This section describes how the language teaching reform was carried out in the programme, the role of the Common Framework for Intercultural Learning, the role of the mentors who accompany students in their learning paths throughout the semester and describes the combined use of these tools.